Performance and Carcass Characteristics of Broiler Chickens Fed Various Components of Candlenut Kernel - Rasid, R. A.; Baba, A. R.; Yaakub, N. M.; Milan, A. R. (Tropical Animal Science Journal, 2019)
One-hundred male broiler chickens (Cobb500) were assigned randomly in a completely randomized design (CRD) into four dietary treatment groups to determine the effects of various components (whole kernel, kernel oil, kernel defatted) of candlenut (Aleurites moluccana) kernel on growth performance, carcass yield, and proximate and fatty acid composition in meat during the grower-finisher stage. Each treatment consisted of 5 replicates with 5 birds for each replications. From 21 to 42 days of age, the birds  were offered either one of the following dietary treatments namely;  Basal diet containing no candlenut kernel (T1), Basal diet containing 2.5% whole candlenut kernel (T2), Basal diet containing 2.5% candlenut kernel oil (T3), and Basal diet containing 2.5% candlenut kernel defatted (T4). The significant difference was determined when the probability level was p